IDENTIFIKASI JENIS KAYU PADA RUMAH ADAT BATAK SIMALUNGUN BERDASARKAN PERSEPSI MASYARAKAT DI DESA NAGORI PURBA KECAMATAN PEMATANG PURBA KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - Citra Helen Patras Purba; M. Mardhiansyah '; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Currently, Batak Simalungun’s traditional house is the only legacy left from the history of the community of the Batak Simalungun. Almost all of the components of the traditional house are made from woods. However over time, the traditional house are started to experience damages in certain places. In this case, one of the efforts made is by knowing the type and criteria of the woods to create the traditional house through public perception. The purpose of this research is to know the type and criteriaof woods with the reason and consideration from the community to recreate Batak Simalungun’s traditional house. This research uses a Snowball Sampling Technique. The results showed that the type of the woods used is Eusideroxylon zwageri, with the criteria are The King’s favorite, big diameter, straight and strong. Some considerations from the community to recreate the Batak Simalungun’s traditional house are the genuine traditional house, have historical value, the house itself is a cultural asset, known by the communities and have been set as cultural heritage. Keywords: Batak Simalungun’s traditional house, Eusideroxylon zwageri